PpMID1 Plays a Role in the Asexual Development and Virulence of Phytophthora parasitica - Hwu, Fang-Yu; Lai, Ming-Wei; Liou, Ruey-Fen (Frontiers in Microbiology, 2017)
Phytophthora parasitica is a notorious oomycete pathogen that causes severe disease in a wide variety of crop species. Infection of plants involves mainly its asexual life stage, including papillate sporangia and biflagellated zoospores, which are the primary dispersal and infection agents of this pathogen. Calcium signaling has been thought as the key regulator for sporangia formation and zoospore differentiation. However, not much is known about the molecular players involved in these processes. In Saccharomyces cerevisiae, mating pheromone-induced death 1 (MID1) encodes a component of a putative calcium channel. Here, we identified and characterized the function of PpMID1, an MID1 homolog from P. parasitica. The expression of PpMID1 was high in sporangia. Gene silencing of PpMID1 resulted in the formation of sporangia that lacked papilla and showed a tendency for direct germination. Notably, in response to cold shock to induce zoospore formation, these sporangia showed no sign of cytoplasmic cleavage and thereby failed to form zoospores. Nonetheless, the addition of CaCl2 or MgCl2 partially recovered the silenced sporangia phenotype, with the formation of papillate sporangia similar to those of the wild type and the release of zoospores upon cold shock. As well, virulence toward Nicotiana benthamiana was reduced in the PpMID1-silenced transformants. These results indicate a role of PpMID1 in the asexual development of P. parasitica.